Subject and Use Index (Bulletin of the Center for Children's Books, 2024)
In the case of subject headings, the subhead "stories" refers to books for the readaloud audience; "fiction," to those books intended for independent reading. Mukwa Anxiety—stories: Kurpiel; Woodruff Apocalypse—fiction: Braun-Arnold; Gillen Art and artists—stories: Hippely; Sukumar Monsters—fiction: Gould; Griffis Mothers—fiction: Egbert Murder—fiction: Stokes Music and musicians—stories: